Professional ethics. Analysis from the Ecuadorian psycho-legal practice. - Francis Bone, Mónica Alexandra (2024)
In today’s world, where the word corruption is commonly associated with a lack of ethical and moral values, as well as the overwhelming human desire to have rather than to be, many of us hold on to the hope of awakening to the light of ethics and conscience, knowing that amidst so much structural violence, something is fundamentally wrong in society.In this context, the professional work of forensic psychologists is not exempt from being corruptible, especially when theoretical foundations that could support or guide their work in the forensic field are lacking.This article aims to encourage self-criticism among forensic psychologists so that, guided by ethical principles, they are motivated to foster meaningful social learning. This involves identifying critical challenges in their practice and committing to improving them to advance in this regard, achieving psycho-legal interventions that are not driven by personal biases or prejudices but rather by a more objective, technical, and, above all, ethical perspective.